Estabilización de una bebida refrescante a partir de aguamiel de agave americana (Agave americana L). - Changoluisa Maigua, Richard Alexis (2020)
The objective of this work was to apply agroindustrial processes to take advantage from agave mead to obtain a refreshing drink stabilized by physical and chemical means. The research consisted to apply different stabilization methods to inhibit yeasts activity and lactic acid bacteria, evaluate their stability during 30 days of storage at room temperature and refrigeration and finally to apply an acceptability test to determine acceptance degree of refreshing drink. The mead was subjected to sterilization (120 ° C for 20 minutes), pasteurization (85 ° C for 30 minutes) with two chemical preservatives sodium metabisulfite (0.1 g / kg), potassium sorbate (0.05%) and stored at two different temperatures respectively. As result of aforementioned methods application eight samples were obtained with their respective repetition, each of the samples were performed physical - chemical (° brix, pH, acidity, turbidity) and microbiological (total mesophiles, molds and yeasts) on the first day, at 15 and 30 days of storage. According to the statistical carried out evaluation through a completely randomized block design a 2x2x2 factorial arrangement, in the INFOSTAT software package determined that the sample t2 sterilization (120 ° C for 30 minutes), sodium metabisulfite (0, 1 g / kg), storage temperature (14 ° C) maintained greater stability during 30 days. To determine the best treatment samples were sent to Chemical Sciences Faculty of Ecuador Central University to carry out a proximal, nutritional and microbiological analysis, finally a tasting test of refreshing drink from agave mead was carried out by Dunnett's test, according to obtained data, drink acceptance by consumers was reflected.